REGIONAL SENSITIVITY OF RURAL HOUSEHOLD FOOD SECURITY: THE CASE OF PUNJAB, PAKISTAN - M. K. Bashir; S. Schilizzi; Ram Pandit (Journal of Animal and Plant Sciences, 2013)
This study aims to examine the regional sensitivity of rural household food security in three regions (South, Central and North) of the Punjab province of Pakistan. We used primary data from 1152 households located in 12 districts of these regions. It was found that food insecurity was highest in the Central region where about 31% of the sample households were measured to be food insecure compared to 13.5% and 15% households in South and North regions, respectively. Econometric analysis revealed that livestock assets have a positive impact on food security across all the three regions while family size has a negative impact. Intermediate and graduation levels of education improve food security in North and Central regions, respectively. In the North region, total number of income earners in the household also positively impacted food security while household heads’ age has an inverse relationship with food security. Results suggest that targeted but region specific policies are needed to improve food security in Punjab
Keywords: food security; regional differences; logistic regression; rural households; Punjab; Pakistan